Osteosynthesis or non-operative treatment of the fibula for distal lower-leg fractures with tibial nailing: a systematic review and meta-analysis. Issue 9 (September 2021) - Frodl, Andreas; Erdle, Benjamin; Schmal, Hagen
Abstract : Fibular fixation to treat distal lower-leg fractures is a controversial intervention. To ensure better stability itself, better rotational stability, and to prevent secondary valgus dislocation – all these are justifications for addressing the fibula via osteosynthesis. High surgical costs followed by increased risks are compelling reasons against it. The purpose of this study was to systematically review the literature for rates of malunion and malrotation, as well as infections and nonunions. We conducted a systematic review searching the Cochrane, PubMed, and Ovid databases. Inclusion criteria were modified Coleman Methodology Score (mCMS) > 60, a distal lower-leg fracture treated by nailing, and adult patients. Biomechanical and cadaver studies were excluded. Relevant articles were reviewed independently by referring to title and abstract. In a meta-analysis, we compared five studies and 741 patients. A significantly lower rate of valgus/varus deviation is associated with fixation of the fibula ( OR = 0.49; 95% CI: 0.29–0.82; p = .006). A higher risk for pseudarthrosis was revealed when the fibula underwent surgical therapy, but not significantly ( OR = 1.46; 95% CI: 0.76–2.79; p = .26). Nevertheless, we noted an increased risk of postoperative wound infection following fibular plating ( OR = 1.90; 95% CI: 1.21–2.99; p = .005). There was no statistically significant difference in the rate of nonunions between the two groups. Overall, the stabilization of the fibula may reduce secondary valgus/varus dislocation in distal lower-leg fractures but is associated with an increased risk of postoperative wound infections. The indication for fibula plating should be made individually. Cite this article: EFORT Open Rev 2021;6:816-822. DOI: 10.1302/2058-5241.6.210003